2020
DOI: 10.32329/uad.741713
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Koha Usage in Bowen University and University of Ilorin Libraries

Abstract: The study is comparative on Koha usage in Bowen University and University of Ilorin Libraries. It adopted a descriptive survey research design. The sample size for the was 50 professional and para-professional librarians who usually make use of Koha Integrated Library System (ILS) at the University of Ilorin library and Bowen University Library (Timothy Olagbenro Library). The questionnaire, interview and observation were used as data collection instruments. The survey was validated while the reliability coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…There have been several efforts to identify which open-source software is most appropriate for library operations. Koha is the most used open-source ILS in university libraries, and the significant justifications for the adoption are user-friendliness, richer features, low cost of purchase, low cost of maintenance, and a support community [21,26,33].…”
Section: Library Automationmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several efforts to identify which open-source software is most appropriate for library operations. Koha is the most used open-source ILS in university libraries, and the significant justifications for the adoption are user-friendliness, richer features, low cost of purchase, low cost of maintenance, and a support community [21,26,33].…”
Section: Library Automationmentioning
confidence: 99%
“…In an investigation of public university libraries in north central Nigeria, only the cataloging routine was automated [16]. Comparing the extent of automation in a private and a public university library; most operations of the private university library were automated, while the public university only had automated cataloguing and circulation [26]. One assessment found that only 5% of university libraries in Nigeria are fully automated, while the remaining 95% are either not automated or partially automated [19].…”
Section: Extent Of Automation In University Libraries' Operationmentioning
confidence: 99%
“…Namun, penerapan sistem informasi KOHA jarang ditemukan pada perpustakaan-perpustakaan di Indonesia, hal ini dikarenakan KOHA perlu konektivitas internet yang memadai, staff yang terlatih, serta membutuhkan perawatan yang tepat (Tunde Omopupa et al, 2019). Selanjutnya kemampuan dalam membaca bahasa pemrograman sangat diperlukan oleh pustakawan perpustakaan, sebab KOHA memiliki proses instalasi dan pengoperasiannya yang dikenal lebih rumit dari pada sistem informasi perpustakaan lain, hal ini dikarenakan KOHA belum dilengkapi dalam versi bahasa Indonesia.…”
Section: 2sistem Informasi Perpustakaan Kohaunclassified